2001
DOI: 10.1042/cs1000613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a phytoestrogen food supplement on reproductive health in normal males

Abstract: Animal studies and human intervention trials have demonstrated the cancer chemopreventive properties of plant phytoestrogens, and phytoestrogen supplements are now widely available 'over-the-counter'. However, consumption of phytoestrogen-rich diets can cause impaired fertility and reproductive tract disorders in some animals and the apparent decline in human sperm quality over recent decades may be related to increased exposure to environmental endocrine disruptors. The present study determines the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 35 publications
5
89
1
4
Order By: Relevance
“…Evidence coming from animal models [102] and human studies has shown that increasing levels of phytoestrogens intake can disrupt both the normal development [103] and the function of the male reproductive system [80]. However, we have found only one report in which adult males were given phytoestrogen supplements (isoflavone) and only for a short period of time (20 days) without finding an effect on semen quality [104].…”
Section: Xenoestrogensmentioning
confidence: 44%
“…Evidence coming from animal models [102] and human studies has shown that increasing levels of phytoestrogens intake can disrupt both the normal development [103] and the function of the male reproductive system [80]. However, we have found only one report in which adult males were given phytoestrogen supplements (isoflavone) and only for a short period of time (20 days) without finding an effect on semen quality [104].…”
Section: Xenoestrogensmentioning
confidence: 44%
“…Simultaneously, some authors reported that there are no significant effects of phytoestrogens in rodents (Roberts et al, 2000;Mitchell et al, 2001;Lamartiniere et al, 2002). One of the explanations for these inconsistent results is that commercial rodent diets all contain high and variable levels of abundant phytoestrogens, which could affect results of studies on reproductive toxicity of test phytoestrogens (Odum et al, 2001;Stroheker et al, 2003;Naciff et al, 2004;Thigpen et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…A report from Mitchell et al limited to only 14 individuals, showed no influence on semen quality or sexual hormones in young males orally consuming 40 mg/day of soy-isoflavones (i.e. genistein, daidzein, glycitein), for 2 months (Mitchell et al, 2001). To add more confusion, an in vitro study showed that low concentrations of genistein (1, 10 and 100 nM) caused an accelerated capacitation and acrosome loss in human spermatozoa (Fraser et al, 2006).…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%